Creation and Accumulation of Radiation Defects in Single Crystals of Magnesium Oxide Research Aims and Methodology - Surzhikov A. P. Anatoly Petrovich (Cham, Springer Nature Switzerland AG, 2024)
Заглавие с титульного экрана